Effects of Different Toothpastes on the Nanomechanical Properties and Chemical Composition of Resin-Modified Glass Ionomer Cement and Composite Resin Restorations - Mariana Dias Moda; Paulo Henrique Dos Santos; Nubia Inocencya Pavesi Pini; Leonardo Negri Furini; André Luiz Fraga Briso; André Assmann; Ticiane Cestari Fagundes (MDPI AG, 2023)
Purpose: This study evaluates the effects of different toothpastes on the nanohardness and chemical compositions of restorative materials and dental surfaces. Methods: Bovine enamel (n = 72) and dentin (n = 72) blocks were obtained and restored using RMGIC (n = 36) or CR (n = 36) to create the following surfaces: dentin adjacent to RMGIC (DRMGIC), enamel adjacent to RMGIC (ERMGIC), dentin adjacent to CR (DCR), and enamel adjacent to CR (ECR). After restoration, one hemiface of each specimen was coated with an acid-resistant varnish to facilitate the creation of control (C) and eroded (E) sides; the latter were achieved by erosion-abrasion cycles as follows: erosion with 1% citric acid: 5 days, four times for 2 min each day; 1% citric acid/abrasion, two times for 15 s, followed by immersion in a toothpaste slurry for 2 min. Toothpastes without fluoride (WF; n = 12), with sodium fluoride (NaF; n = 12), and with stannous fluoride (SnF2; n = 12) were used for RMGIC or CR. The specimens were analyzed for nanohardness (H), and chemical composition using energy-dispersive X-ray spectroscopy and Raman microscopy. The data were statistically analyzed using two-way repeated measures ANOVA and Tukey's test (α = 0.05). Results: Lower H values were obtained with NaF for DRMGIC-C, with a statistically significant difference from the H value obtained with WF (p < 0.05). The calcium and phosphorus concentrations in DCR-E were significantly lower with WF than with the other types of toothpaste (p < 0.05). Fluoride-containing toothpastes are capable of preserving the main chemical components of the dentin adjacent to the restorative materials under erosive-abrasive conditions.